أثر استخدام التكنولوجيا في تنمية السلوك المقاولاتي : The effect of using technology on developing entrepreneurial behavior - محفوظ هنداوي; رمضان خماخم (Journal of North African Economies, 2025)
This study aims to know the effect of using technology on developing entrepreneurial behavior, while highlighting the mediating role that entrepreneurial intention plays in developing entrepreneurial behavior. The study used the experimental method, where the study was conducted on 1128 university students representing 12 Algerian universities. Structural modeling was used in data analysis through the (AMOS24) program. The results of the study concluded that the use of technology has a significant impact on enhancing entrepreneurial intention and entrepreneurial behavior, with a focus on the frequency of technological use and the nature of the content. The study recommended decision-makers to generalize education to use technology for all educational stages, regardless of specializations, to raise the level of use to look forward to more entrepreneurial opportunities.